Maybe u should do inverse operation on both sides idk but just try it
Y = -2 x - 9
3 x - 4(-2 x - 9 ) = -8
3 x + 8 x + 36 = - 8
11 x = - 44, x = - 4
y = 8 - 9 , y = -1
This is a unique solution, the system is independent.
Answer:
10!
Step-by-step explanation:
Because I ate chicken nuggets!
The correct answer is option B which is the function will be
f(n) = -6.25+0.75n.
<h3>What is a function?</h3>
A function is defined as the expression that set up the relationship between the dependent variable and independent variable.
Given series is as follows:-
-5.5, -4.75, -4, -3.25, ...
When we use the function:-
f(n) = - 6.25 + 0.75n
f(1) = -6.25 + 0.75 x 1 = -5.5
f(2) = -6.25 + 0.75 x 2 = -4.75
f(3) = -6.25 + 0.75 x 2.25 = -4
Therefore the correct answer is option B which is the function will be
f(n) = -6.25+0.75n.
To know more about function follow
brainly.com/question/25638609
#SPJ1